Impact of Saline Intrusion on Social and Economic Livelihoods of Farmers in the Vietnam Mekong Delta - Van Huynh Thanh Pham; Rudi Febriamansyah; Afrizal Afrizal; Thong Anh Tran (International Journal of Agricultural Sciences, 2017)
One of the effects of global climate change is the increasing sea level, which has resulted in higher intrusion of sea water to the mainland in the Mekong Delta region in Vietnam. This study specifically explores the impact of saline intrusion on the socio-economic life of farmers in this region. A socioeconomic survey was carried out in two provinces in the eastern and western regions of the Delta, namely the Kien Giang province in the West and the Tra Vinh Province in the East which represented two regions, each of which experienced different levels of saline intrusion. Data collection methods include secondary data collection, focused group discussions, expert interviews, key informant interviews and 280 household questionnaire surveys. Technically, saline intrusion has changed the farming system from rice culture to shrimp culture at both sides of the Delta. Because of the need for investment in shrimp culture, a group of farming communities with large capital quickly took the opportunity to move to intensive shrimp culture. Meanwhile, other groups of farmers who lack of capital, are only able to carry out traditional rice-shrimp culture by digging around their paddy field for shrimp pond, with lower economic outcomes from their rice and shrimp production. Weak social organizations in the community, making the impact of saline intrusion is only beneficial for a few groups of people.